Structural-Based Optimizations of the Marine-Originated Meridianin C as Glucose Uptake Agents by Inhibiting GSK-3β - Shuwen Han; Chunlin Zhuang; Wei Zhou; Fener Chen (Marine Drugs, 2021)
Glycogen synthase kinase 3β (GSK-3β) is a widely investigated molecular target for numerous diseases, and inhibition of GSK-3β activity has become an attractive approach for the treatment of diabetes. Meridianin C, an indole-based natural product isolated from marine Aplidium meridianum, has been reported as a potent GSK-3β inhibitor. In the present study, applying the structural-based optimization strategy, the pyrimidine group of meridianin C was modified by introducing different substituents based on the 2-aminopyrimidines-substituted pyrazolo pyridazine scaffold. Among them, compounds B29 and B30 showed a much higher glucose uptake than meridianin C (<5%) and the positive compound 4-benzyl-2-methyl-1,2,4-thiadiazolidine-3,5-dione (TDZD-8, 16%), with no significant toxicity against HepG2 cells at the same time. Furthermore, they displayed good GSK-3β inhibitory activities (IC50 = 5.85; 24.4 μM). These results suggest that these meridianin C analogues represent novel lead compounds with therapeutic potential for diabetes.